Management of change framework with integrated risk analysis for temporary and emergency cases - Pang, Kar Kei (2021)
Process industries overgrow due to increasing demand for petroleum made products.The potential of major accident may significantly increase even more when temporary and emergency change is implemented. In fact, temporary and emergency changes were identified as one of the main contributors to the failure of Management of Change (MOC) in industries, leading to catastrophic outcomes in process industries. However, current MOC implementation and attention, especially towards temporary and emergency, lack in process industries due to inconsistency and different interpretation based on the established standards, time constraint and availability of data.. Corresponding to these weaknesses, an integrated risk analysis framework and system for temporary and emergency change based on PSM is developed. The concept of this research is targeting to provide complete guidance with the aids of documents and software for implementation of temporary and emergency software. Objectives of this research are, to develop temporary and emergency MOC framework, to develop a management system on MOC and to validate frameworks and management system developed through a pilot study. The research process begin with analysing all the requirements in the OSHA PSM standard and including into critical action item in the framework. Framework on temporary and emergency cases is established based on the adopted permanent MOC framework and selected PSM standard requirement. Adopted risk assessment checklists have been proposed with an embedded risk rating to improve risk prioritisation. The developed framework was transformed into a model known as Management of Change Management System (MOCMS) to improve tracking of open and expiring temporary MOC case and ease the process to retrieve information. The validation process of developed framework and system have been conducted through a pilot study by obtaining real data from process plant and testing applicability of developed result by repeating real-life temporary change case using developed framework and software. Meanwhile interview session has been conducted to obtain user and expert feedbacks on the developed results.Results of this study comprised of an overview of the MOC process displayed by a PDCA cycle, a complete MOC process framework with an adopted checklist, and a MOC management system acting as a guidance and documentation software. In overall, the developed framework has complied with the current practice in real process plant where all the necessary forms and checklist used are covered in the developed framework. Besides, the developed framework has proposed more comprehensive and detailed action items, such as specific risk assessment for organisational change and detailed risk assessment checklist in technical and technological change. In addition, the developed management system equipped with the features of recording time taken for every action item has successfully tracked the time taken for a specific action item. It is found that the time required for the completion of risk assessment in the developed framework is relatively shorter than the original MOC risk assessment process. Therefore, the pilot study has confirmed the MOC framework met critical elements in the MOC of selected MOC regulation with improvement to identified issues. The performance of the MOC framework and software shall be measure on the timely completion of MOC action items, and improvement in In contrast, the management system is reliable to improve system documentation and information storage.